Characteristics and controls of an offshore freshened groundwater system in the Shengsi region, East China Sea - Thomas, Ariel T.; Micallef, Aaron; Duan, Shuangmin; Zou, Zhihui (Frontiers in Earth Science, 2023)
Offshore freshened groundwater (OFG) has been encountered in continental margins around the world and identified as a potential unconventional water resource. In China, coastal areas and islands face limited freshwater resources. The East China Sea, specifically the region north of Shengsi islands, may contain an OFG system hosted in buried paleochannels associated with the ancient Yangtze river. To assess the OFG potential, characteristics, and controls in this region, we employed an integrated modeling approach. We constructed a 2D geological model of Quaternary sediments based on data from two well sites. By considering sea-level fluctuations over the past 200,000 years, we conducted a paleo-reconstruction of groundwater flow and solute transport conditions on the 2D transect. We compared the simulated present-day distribution of OFG in the model with borehole observations. Our findings indicate that the region was mostly sub-aerially exposed during the simulated period, allowing for potential meteoric recharge. Numerical results demonstrate a high likelihood of a laterally extensive OFG system existing today. The mechanism responsible for its formation appears to be meteoric recharge and offshore directed groundwater flow caused by increased hydraulic gradients during sea-level lowstand. The model suggests that the OFG system forms an oceanward dipping wedge, with the top occurring approximately 50–100 m below the seafloor. Freshwater is likely present down to the basement at around 250 m. The geometry and volume of the OFG system are strongly influenced by the shelf stratigraphy. We estimate the volume of freshwater in the region to range from 0.5 to 1.6 km3 km-1, indicating a viable potential freshwater resource for the Shengsi region and coastal city of Shanghai. To gain further insights, we recommend conducting additional investigations using geophysical techniques.